Is resection of colorectal liver metastases after a second-line chemotherapy regimen justified? - Brouquet, Antoine (2011)
BACKGROUND: Patient outcomes following resection of colorectal liver metastases (CLM) after second-line chemotherapy regimen is unknown. METHODS: From August 1998 to June 2009, data from 1099 patients with CLM were collected prospectively. We retrospectively analyzed outcomes of patients who underwent resection of CLM after second-line (2 or more) chemotherapy regimens. RESULTS: Sixty patients underwent resection of CLM after 2 or more chemotherapy regimens. Patients had advanced CLM (mean number of CLM ± standard deviation, 4 ± 3.5; mean maximum size of CLM, 5 ± 3.2 cm) and had received 17 ± 8 cycles of preoperative chemotherapy. In 54 (90%) patients, the switch from the first regimen to another regimen was motivated by tumor progression or suboptimal radiographic response. All patients received irinotecan or oxaliplatin, and the majority (42/60 [70%]) received a monoclonal antibody (bevacizumab or cetuximab) as part of the last preoperative regimen. Postoperative morbidity and mortality rates were 33% and 3%, respectively. At a median follow-up of 32 months, 1-year, 3-year, and 5-year overall survival rates were 83%, 41%, and 22%, respectively. Median chemotherapy-free survival after resection or completion of additional chemotherapy administered after resection was 9 months (95% confidence interval, 4-14 months). Synchronous (vs metachronous) CLM and minor (vs major) pathologic response were independently associated with worse survival. CONCLUSIONS: Resection of CLM after a second-line chemotherapy regimen was found to be safe and was associated with a modest hope for definitive cure. This approach represents a viable option in patients with advanced CLM. Cancer 2011;. © 2011 American Cancer Society.